ROLE OF INFORMATION IN ECONOMIC GLOBALIZATION (Scientific journal of the Fergana State University, 2025)
In this article, the role of information in the globalization of the economy, the introduction of information-communication and computer technologies and their rapid development, bringing great changes to our society, the formation of a common information society in the world, the importance of information in the economic sphere , it was analyzed that ensuring fast and high-quality circulation of information becomes a key criterion for the development and prosperity of the country.